2002
DOI: 10.1111/j.1651-2227.2002.tb03333.x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in infants with chronic lung disease after treatment with dexamethasone

Abstract: The aim of this study was to study the effect of chronic lung disease (CLD) and dexamethasone treatment on body composition in preterm infants (birthweight > 1500g). In addition, anthropo‐metric measurement of body composition were compared with dual‐energy X‐ray absorptiometry (DXA). Fourteen preterm infants with CLD and a comparison group of 18 preterm infants were studied until 3 mo corrected age. CLD infants received approximately 20 kcal kg‐1 per day extra nutritional intake during dexamethasone treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…When corticosteroids are used, increased caloric intake during therapy may improve growth and help mitigate their bone demineralizing effects. 32 In light of our observation that postnatal growth restriction is associated with increased odds of severe MBD, these findings may be of particular importance.…”
Section: Discussionmentioning
confidence: 85%
“…When corticosteroids are used, increased caloric intake during therapy may improve growth and help mitigate their bone demineralizing effects. 32 In light of our observation that postnatal growth restriction is associated with increased odds of severe MBD, these findings may be of particular importance.…”
Section: Discussionmentioning
confidence: 85%
“…Our study is the first to report bone mass after exposure to antenatal betamethasone. Five studies have reported bone mass in the first year of life after postnatal exposure to glucocorticoids for neonatal chronic lung disease (33–37) . Three reported no difference in bone mass after dexamethasone (33–35) .…”
Section: Discussionmentioning
confidence: 99%
“…Five studies have reported bone mass in the first year of life after postnatal exposure to glucocorticoids for neonatal chronic lung disease (33–37) . Three reported no difference in bone mass after dexamethasone (33–35) . One reported a negative association between duration of dexamethasone treatment and BMC at 3 months corrected age, (36) and the other also reported lower BMC in dexamethasone‐treated preterm infants (37) .…”
Section: Discussionmentioning
confidence: 99%
“…body composition in preterm infants when it was used to treat chronic lung disease (Bolt et al, 2002). Furthermore, Gilmour et al demonstrated that Dex did not affect body composition of term gestational age infants despite the negative influences on glucose metabolism and growth patterns after drug exposure (Gilmour et al, 1995).…”
Section: Discussionmentioning
confidence: 99%